Efficacy and Safety of Erenumab in Adults With Medication Overuse Headache: Final Results From a Phase 4 Randomized Placebo-Controlled Study - Tepper, Stewart J; Dodick, David W; Lanteri-Minet, Michel; Dolezil, David; Gil-Gouveia, Raquel; Lucas, Christian; Piasecka-Stryczynska, Karolina; Szabó, Gyöngyi; Mikol, Daniel D; Chehrenama, Mahan; Chou, Denise E; Liu, Zilu; et al. (European journal of neurology, 2025)
BACKGROUND: Erenumab-induced medication overuse headache (MOH) remission in participants with chronic migraine (CM) in a prospective, Phase 4, randomized, placebo-controlled trial with an open-label treatment period (OLTP). We present 1-year results from the combined double-blind treatment period (DBTP) and OLTP for the stratified nonopioid cohort. METHODS: Participants with CM-MOH were randomized 1:1:1 to subcutaneous 70 or 140 mg erenumab every 4 weeks (QM) or placebo for the initial 24 weeks (DBTP). Those successfully completing DBTP could continue the 28-week OLTP, maintaining the same erenumab dose received during DBTP or, if receiving placebo, randomly assigned 1:1 to erenumab 70 or 140 mg QM. OLTP endpoints were exploratory. RESULTS: Overall, 552 participants received erenumab (70 mg, n = 274; 140 mg, n = 278); 95.3% completed OLTP. One-year MOH relapse in participants who achieved MOH remission at DBTP Month 6 was 2.7% (3/111) and 2.4% (3/124) with erenumab 70 and 140 mg, respectively; absence of MOH at study end was observed in 69.0% (189/274) and 75.5% (210/278) of participants. Sustained MOH absence over 1 year was reported in 60.5% (107/177) and 68.8% (119/173) of participants, respectively. Sustained improvements in measures of headache days, medication days, and function were observed in both groups. No new safety concerns were identified (grade ≥ 3, 35 [6.3%]; serious, 17 [3.1%]; adverse events leading to treatment discontinuation, 5 [0.9%]). CONCLUSIONS: Erenumab was effective in inducing and sustaining MOH remission and improving function over 1 year. Treatment compliance remained high, with safety events consistent with erenumab's known safety profile. TRIAL REGISTRATION: NCT03971071.
Keywords: dospělí; antagonisté CGRP receptorů; Female; sekundární bolesti hlavy; Adult; calcitonin gene‐related peptide; výsledek terapie; ženské pohlaví; Migraine Disorders; Calcitonin Gene-Related Peptide Receptor Antagonists; migréna; lidé; erenumab; dvojitá slepá metoda; migraine disorders; headache disorders; Treatment Outcome; Double-Blind Method; Male; secondary; Headache Disorders, Secondary; lidé středního věku; humanizované monoklonální protilátky; clinical trial; Antibodies, Monoclonal, Humanized; mužské pohlaví; Middle Aged; Humans